ANALYSIS OF â€œLOVE DAWNâ€ MOVIE ON ISLAMIC VALUES (A LITERATURE STUDY) - Tawvicky Hidayat (Bayan lin-Naas : Jurnal Dakwah Islam, 2023)
Abstract: Study This aim For know message preaching on film Trilogy Love Dawn Movie. Islamic message scene related to shari`ah, creed, and morals. The meaning contained in the film Love Dawn Movie's production is to visualize when Ratih decides Angga, regarding relationships with the opposite sex, is only about true love to Allah and His Messenger, belief that guidance belongs only to Allah, and ethics preach. Meanwhile, the connotation means the message of preaching not to approach zina, her message of preaching to become obedient Muslim women, adds to the taste love for Allah and His Messenger, adds to the belief that guidance is only yours Allah, And ethics a Muslim in preach.keywords : Da'wah, Love Dawn.